2008
DOI: 10.1289/ehp.11268
|View full text |Cite
|
Sign up to set email alerts
|

Low-Level Human Equivalent Gestational Lead Exposure Produces Supernormal Scotopic Electroretinograms, Increased Retinal Neurogenesis, and Decreased Retinal Dopamine Utilization in Rats

Abstract: BackgroundPostnatal lead exposure in children and animals produces alterations in the visual system primarily characterized by decreases in the rod-mediated (scotopic) electroretinogram (ERG) amplitude (subnormality). In contrast, low-level gestational Pb exposure (GLE) increases the amplitude of scotopic ERGs in children (supernormality).ObjectivesThe goal of this study was to establish a rat model of human equivalent GLE and to determine dose–response effects on scotopic ERGs and on retinal morphology, bioch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(41 citation statements)
references
References 49 publications
2
39
0
Order By: Relevance
“…One explanation for the delayed response evident in the Pb 2+ -exposed larvae (Fig. 3A) is an increase in the sensory threshold of the lateral line neuromasts, as observed in frog and rat retinal cells exposed to Pb 2+ (Fox et al 2008; Fox et al 1991; Fox and Sillman 1979). Second, depressed neuronal function also may have occurred in the descending interneurons that connect the M-cell to the lateral trunk muscles.…”
Section: Discussionmentioning
confidence: 85%
“…One explanation for the delayed response evident in the Pb 2+ -exposed larvae (Fig. 3A) is an increase in the sensory threshold of the lateral line neuromasts, as observed in frog and rat retinal cells exposed to Pb 2+ (Fox et al 2008; Fox et al 1991; Fox and Sillman 1979). Second, depressed neuronal function also may have occurred in the descending interneurons that connect the M-cell to the lateral trunk muscles.…”
Section: Discussionmentioning
confidence: 85%
“…There were no changes in scotopic and photopic ERG a-waves measured either at the peak or at 10 ms. The latter measure is thought to reflect the function of the photoreceptors without the contribution of other retinal cells (Fox et al 2008, Jamison et al 2001). The flicker ERG amplitudes recorded with UV or green lights were unchanged, suggesting that the function of S-cones and M-cones was not altered by toluene.…”
Section: Discussionmentioning
confidence: 99%
“…Parameters analyzed included the peak latencies of the a-wave and b-wave, the a-wave amplitude (measured baseline to peak) and the b-wave amplitude (measured trough-to-peak from a-wave to b-wave). In addition, an alternative measurement of a-wave amplitude was obtained at 10 ms after the flash, which was thought to better reflect the function of only rod photoreceptors prior to the onset of neural activity from other retinal cells (Fox et al 2008, Jamison et al 2001). …”
Section: Methodsmentioning
confidence: 99%
“…Fox et al (1997) demonstrated that there were age-and dose-dependent decreases in the rod a-wave and b-wave sensitivity and maximum amplitudes without any effect on cones in developmentally and adult lead-exposed rats in a subsequent study [6]. Recently, Fox et al (2008) have reported a dose-dependent effect of gestational lead exposure in rats, with low and moderate dosing causing supernormal scotopic ERGs, in contrast to reduced scotopic ERGs seen after high-level gestational exposure [7]. In adult rats exposed to lead for 3 weeks, qualitatively similar ERG changes occurred in the absence of cell loss or decrease in rhodopsin content [6].…”
Section: Discussionmentioning
confidence: 99%